Urban Growth in Germany – The Impact of Localization and Urbanization Economies - Annette Illy; Christoph Hornych; Michael Schwartz; Martin T. W. Rosenfeld (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2009)
This study examines the impact of localization and urbanization economies as well as the impact of city size on urban growth in German cities from 2003 to 2007. Although, from a theoretical perspective, agglomeration economies are supposed to have positive impacts on regional growth, prior empirical studies do not show consistent results. Especially little is known about agglomeration economies in Germany, where interregional support policy and the characteristics of the federal system are further determinants of urban growth. The results of the econometric analysis show a Ushaped relationship between specialization and urban growth, which particularly holds for manufacturing industries. We do not find evidence for the impact of Jacobs-externalities; however, city size shows a positive (but decreasing) effect on urban growth. – – Diese Studie untersucht den Einfluss von Lokalisationsund Urbanisierungseffekten sowie den Einfluss der Stadtgröße auf das Wachstum deutscher Städte im Zeitraum von 2003 bis 2007. Obwohl aus theoretischer Sicht Agglomerationsvorteile als förderlich für regionales Wachstum gelten, ergeben bisherige empirische Untersuchungen diesbezüglich kein einheitliches Bild. Insbesondere liegen bisher kaum Ergebnisse für Deutschland vor. Hier stellen auch die interregionale Ausgleichspolitik sowie die Besonderheiten des föderalen Systems Determinanten des Stadtwachstums dar. Die Ergebnisse der durchgeführten ökonometrischen Untersuchung für die Städte in Deutschland deuten auf eine Uförmige Beziehung zwischen Spezialisierung und Stadtwachstum hin. Dieser Zusammenhang zeigt sich insbesondere im Verarbeitenden Gewerbe. Hinweise auf die Wirkung von JacobsExternalitäten können nicht nachgewiesen werden, wenngleich von der Stadtgröße ein positiver (jedoch abnehmender) Effekt auf das urbane Wachstum ausgeht.
urn:nbn:de:101:1-20091222764
Keywords: O18; R11; R12; R15; 330; Agglomeration; Localization economies; Urbanization economies; Urban Growth; Specialization; Diversification; Agglomeration; Lokalisationseffekte; Urbanisierungseffekte; Städtewachstum; Spezialisierung; Diversifikation; Stadtwachstum; Lokalisationseffekt; Agglomerationseffekt; Urbanisierungseffekt; Schätzung; Deutschland